Is Colombia a violent country? (Colombia Medica, 2017)
In this article by Fandiño-Losada and  Guerrero  (Colomb Med (Cali). 2017;48(1): 9-11), On page 10, Figure 1, x axis name is incorrect: “Rate x 1,000 K hab.” The correct name should have read: “Rate x 100,000 hab.” Fe errata